THE NEWSPAPER «POKUTTYA» AND ITS ROLE IN SETTING UP THE SYSTEM OF UKRAINIAN PRESS FUNCTIONING IN THE INTERWAR PERIOD IN HUTSUL-POKUTTYA REGION - Vasylchuk, M. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The author scrutinizes the peculiarities of Ukrainian press functioning at the beginning of the 1920-s after Polish occupation of Halychyna. The circumstances, where the Ukrainians won their right back for free speaking out, partly through the mass media, are depicted here. The role and the importance of press as a very important factor in saving Ukrainian national identity, striving for sovereignty, fiction literature development in Hutsul-Pokuttya region are opened.